Bioethical topics in the works of Kvirin Vasilj (1917 – 2006) - Tomić, Draženko (Array, 2020)
Kvirin Vasilj (1917 – 2006), an authentic thinker of the 20th century, in his philosophical deliberation, he touches on various aspects of human existence, including those that are today identified as bioethical challenges. Thus, bioethics is present in his deliberations, although the term bioethics as such is not found in any of his six hundred works, and they often relate to the meaning, quality, the beginning and the end of human life. Between these two endpoints of an individual’s existence, Vasilj places a considerable emphasis on the very practical dimensions of duration, nature protection, quality of life and more. It should also be noted that Vasilj often uses these themes as a basis on which to present or explain some anthropological, even ontological, issues.